Lying and team incentives - Julian Conrads; Bernd Irlenbusch; Rainer Michael Rilke; Gari Walkowitz (Institute for the Study of Labor (IZA), 2011)
We investigate the influence of two widespread compensation schemes, individual piece-rates and team incentives, on participants' inclination to lie, by adapting the experimental setup of Fischbacher and Heusi (2008). Lying turns out to be more pronounced under team incentives than under individual piece-rates, which highlights a so far fairly neglected feature of these compensation schemes.
urn:nbn:de:101:1-201110102151
Keywords: C91; C92; M52; 330; compensation schemes; lying; team; experiment; Arbeitsgruppe; Vergütungssystem; Ökonomischer Anreiz; Kommunikation; Test